An Analysis of Character Education in “English for Nusantara” Textbook for Eight Grade Students - Tahrun; Indri Nurhasanah; Aty Hartati (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This paper was to analyze character education principles embedded in the English textbook "English for Nusantara" for eighth grade students in line with the Merdeka curriculum, explain skills embedded in learning resources covering six dimensions in Pancasila student profile. The study's subjects were English conversation scripts and images from English for Nusantara textbooks. The writers use a checklist as a tool for gathering data. One of the goals of the Merdeka curriculum is to create a Pancasila student profile, which the author employs the values of the Pancasila student profile established by the Republic of Indonesia's Ministry of Education and Culture. The Pancasila Student Profile's six dimensions were used to classify the characters from the textbook. The study identified six Pancasila Student Profile dimensions. The dimensions measured include faith, fear of God, noble character (24.96%), global variety (14.74%), mutual collaboration (13.16%), independence (20.4%), critical thinking (19.12%), and creativity (9.71%). The Pancasila Student Profile has 20 aspects across six dimensions. The characters in this book are primarily implicitly integrated. The "English for the Nusantara" textbook emphasized faith, fear of God, and noble character. Furthermore, the textbook emphasized the importance of manners towards others. According to Prismarani's (2014) character education classification, this textbook received a perfect score of 100%, indicating very high' quality.